Morphology and morphometric diversity of three local goats in Gorontalo, Indonesia - FAHRUL ILHAM; GATOT CIPTADI; TRI EKO SUSILORINI; WIDYA PINTAKA BAYU PUTRA; SUYADI SUYADI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Ilham F, Ciptadi G, Susilorini TE, Putra WPB, Suyadi S. 2023. Morphology and morphometric diversity of three local goats in Gorontalo, Indonesia. Biodiversitas 24: 1366-1375. This research aimedto identify morphology and morphometric, as well as body indices and measurements markers, for use inlocal goats selection program in Gorontalo, Indonesia. The samples consisted of 37 Etawah Crossbreed, 96 Local Gorontalo, and 40 Kacang goats raised by traditional semi-intensive breeders. The morphological variables observed included feather color, color combination pattern, nose, ear shape, horn, beard, tail direction, and morphometric variables observed were withers height, hip height, hip width, body length, chest width, chest depth, chest girth, ear length, and ear width. The qualitative morphology was analyzed with descriptive method with Chi-squared test. While, the morphometrics of goat was used for calculating the body indices and principal component analysis.The results of the chi-square analysis showed significant differences in qualitative morphology among the three observed breeds (p<0.05), except for the presence of horns, beards, and the direction of the tail. The body measurements of Local Gorontalo goats were significantly different from those of Kacang goats except for chest depth. The only difference between the Etawah Crossbreed and the other two breeds included body weight,wither height, hip height, body length, ear length,and ear width (p<0.05). The three local goats had a long body length and legs, with a waist higher than the shoulders. Meanwhile,the medigline classification was only for Local Gorontalo and Kacang goats that had good thoracic development. The conformation index of the three local goat breeds had a significant correlation with body weight. The variables with the best contribution from the first component that can be considered sequentially in the selection program for Etawah Crossbreed goats, Local Gorontalo, and Kacang goats were body length, chest girth, and wither high. For the second component, the variables included ear length and chest width, while that of the third component in Kacang goats wasear length.